Solidarity in Times of Crisis - Boutabia, Amina (International Journal of Language and Literary Studies, 2022)
The concept of solidarity is certainly one of the most challenging among the concepts forming the constellation of social and political thought. Not only because of its use in a variety of discourses, but also because it is one of the most influential concepts despite the fact that it is still undertheorized. At the heart of the complexity is the ambiguity between the normative and descriptive usages of the concept. It seems that this ambiguity is clearly reflected in this time of Covid-19 pandemic which has revealed that both individuals and nations can demonstrate both solidary and anti-solidary actions simultaneously. This paper is an attempt to understand these contradictory conducts in the light of the history and development of the concept. Thus, the following questions are addressed: First, at a macro level, why do many countries behave towards each other in an anti-solidary manner? Second, why do individuals, despite their denomination and learning show a lack of solidarity towards the most unfortunate people? Solidarity ethics appears in religious, philosophical, and humanitarian discourses, so, what makes these discourses extremely ineffective in times when solidarity is most needed?